On‐ versus off‐pump CABG in octogenarians: A propensity‐matched analysis from the UK National Database. Issue 12 (2nd November 2022) - Chan, Jeremy; Dimagli, Arnaldo; Fudulu, Daniel P.; Dong, Tim; Mikova, Ester; Angelini, Gianni D.
Abstract: Introduction: Coronary artery bypass grafting (CABG) remains a good revascularization strategy in octogenarians with excellent clinical outcomes and quality of life postoperatively. However, the benefits of off‐pump over on‐pump CABG in the elderly population are still controversial. We investigated this issue in the UK National Audit database. Method: We retrospectively analyzed all octogenarians undergoing nonemergency, isolated CABG from 1996 to 2019. Propensity score matching (PSM) was conducted to adjust for imbalance in the baseline characteristics between the off‐pump and on‐pump groups. Primary outcome was in‐hospital mortality and postoperative cerebrovascular accidents. Secondary outcomes were bleeding requiring reoperation, deep sternal wound infection, and postoperative dialysis. Result: A total of 6436 patients were included for analysis. No differences were observed between off‐ and on‐pump group in‐hospital mortality (4% vs. 3.8%, p = .89), return to theater rate (5.4% vs. 6.2%, p = .16) and incidence of deep sternal wound infection (1.1% vs. 1.6%, p = .34). However, octogenarian undergoing off‐pump CABG were less likely to experience postoperative transient ischemic attack (TIA)/stroke (1.4% vs. 2.3%, p = .004) but more likely to require renal dialysis (4.8% vs. 3.5%, p = .03). Conclusion: The data show similar in‐hospital mortality in octogenarians regardless of the revascularization technique used. Off‐pump when compared with on‐pump CABG is associated with a lower incidence in postoperative neurological events but a higher need for renal dialysis.